Calling ecology of micro frogs (Microbatrachella capensis): a case study using acoustic spatial capture recapture - Gedert, Jennifer (Department of Biological Sciences, 2021)
Amphibians worldwide are declining, increasing the demand for monitoring populations of many threatened amphibians, including the South African Critically Endangered micro frog (Microbatrachella capensis). I attempted to improve ongoing monitoring efforts by determining the calling ecology of the micro frog population on the Cape Flats. I used acoustic spatial capture recapture to calculate call density and identify the main factors that determine periods of maximum frog calls. Increased calling behaviour was found early in the season and in response to rainfall. In addition, micro frogs were found to call more at night than during the day. This suggests that future monitoring of this species should occur at night, after rain, and early in the winter breeding season. From the call density estimates, I calculated the size of the micro frog population on the Cape Flats to be about 200 adult frogs when an equal sex ratio of adult males and females is assumed. Future monitoring and conservation efforts should take into consideration this baseline population estimate and keep track of any demographic trends in the population.